Transformasi Sosial dalam Konteks Urbanisasi dan Modernisasi di Indonesia - Yulianti, Heni; Ningsih, Dewi Puspita; Apriawan, Andika (INDO PUBLISHING, 2025)
Social transformation in Indonesia is closely linked to the dynamics of urbanization and modernization, which have intensified over the past two decades. Urbanization has led to structural changes across economic, social, and cultural dimensions, including the emergence of new urban areas, shifts in family structures, and changes in societal values and identity. This study aims to examine how urbanization and modernization shape patterns of social transformation in Indonesia through a systematic literature review and secondary data analysis from official reports and recent academic publications. The findings indicate that urbanization produces ambivalent implications: on one hand, it creates opportunities for economic growth and global integration; on the other, it exacerbates social inequality, marginalization, and cultural challenges. Modernization, accelerated through infrastructure development and the relocation of the national capital, highlights the complex relationship between social transformation and development policies. These findings are expected to contribute to the discourse on sustainable and inclusive urban development in Indonesia.